CORRELATION BETWEEN TEACHER’S LIKABILITY AND ATTITUDE TOWARDS ACCOUNTING AMONG SECONDARY SCHOOL STUDENTS IN ENUGU STATE - Abiakwe, Angela C. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
The present paper examined the relationship between teachers' likeability and attitudes towards accounting among secondary school students in Enugu state. One hundred and forty-two (n=142) male and female senior secondary school students conveniently pooled from public and private secondary schools in Enugu state participated in the survey. The respondents completed the self-report measures of the teacher's likeability and accounting attitudes scale. A simple regression analysis was performed on the data to test the assumed interaction between teachers' likeability and students' attitudes towards accounting. The result of the linear regression analysis established a statistically significant interaction effect between teacher's likeability and student's attitude towards accounting, F (1,140), 24.71 P< .05 with adjusted R2 of 183, revealing that teacher's likeability contributed about 18.3% of the variation of student's attitude towards accounting. The finding and practical implications are discussed.